Metallic magnetic cores and inductors

JP7632718B2Active Publication Date: 2025-02-19MURATA MFG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024040080
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-03-14
Publication Date
2025-02-19
Estimated Expiration
2040-03-27

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、絶縁性及び直流重畳特性に優れた金属磁性粒子及びインダクタ、絶縁性及び直流重畳特性に優れた金属磁性粒子を得ることのできる金属磁性粒子の製造方法、並びに、絶縁性及び直流重畳特性に優れた金属磁性体コアを得ることのできる金属磁性体コアの製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007632718000003
    Figure 0007632718000003
  • Figure 0007632718000004
    Figure 0007632718000004
  • Figure 0007632718000005
    Figure 0007632718000005
Patent Text Reader

Abstract

To provide: a metal magnetic particle and an inductor that have excellent insulation properties and direct-current superposition characteristics; a method for manufacturing a metal magnetic particle capable of obtaining a metal magnetic particle having excellent insulation properties and direct-current superposition characteristics; and a method for manufacturing a metal magnetic core capable of obtaining a metal magnetic core having excellent insulation properties and direct-current superposition characteristics.SOLUTION: A metal magnetic particle (1) is provided with an oxide layer on a surface of an alloy particle (10) containing Fe and Si. The oxide layer has a first oxide layer (20), a second oxide layer (30) and a third oxide layer (40) from a side of the alloy particle. In line analysis of element content by using a scanning transmission electron microscope-energy dispersive X-ray spectroscopy, the first oxide layer (20) is a layer where Si content takes a local maximum value, the second oxide layer (30) is a layer where Fe content takes a local maximum value, and the third oxide layer (40) is a layer where Si content takes a local maximum value.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a metal magnetic particle, an inductor, a method for manufacturing a metal magnetic particle, and a method for manufacturing a metal magnetic core. [Background technology]

[0002] Power inductors used in power supply circuits are required to be smaller, have lower loss, and be able to handle large currents. To meet these requirements, the use of metal magnetic particles with high saturation magnetic flux density as the magnetic material has been considered. While metal magnetic particles have the advantage of high saturation magnetic flux density, the insulation resistance of the material itself is low, so in order to use them as magnetic materials in electronic components, it is necessary to ensure insulation between the metal magnetic particles. For this reason, various methods for improving the insulation properties of metal magnetic particles have been investigated.

[0003] For example, Patent Document 1 discloses a method of coating the surfaces of metal magnetic particles with an insulating film such as glass, and Patent Document 2 discloses a method of forming an oxide layer derived from the material on the surfaces of metal magnetic particles. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 5082002 [Patent Document 2] Patent No. 4866971 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the method described in Patent Document 1 has the problem that it is not possible to form an insulating film such as glass uniformly on the surface of the metal magnetic particles, and areas with thin film thickness become the starting point of dielectric breakdown. Furthermore, the method described in Patent Document 2 has the problem of insufficient insulation reliability because the oxide layer derived from the raw material potentially contains defects. Also, the metal magnetic material described in Patent Document 2 has the problem of being unable to be heat-treated at high temperatures to prevent the oxidation of the raw material particles from progressing.

[0006] The present invention aims to provide metal magnetic particles and inductors with excellent insulation and DC bias characteristics, a method for manufacturing metal magnetic particles that can produce metal magnetic particles with excellent insulation and DC bias characteristics, and a method for manufacturing metal magnetic cores that can produce metal magnetic cores with excellent insulation and DC bias characteristics. [Means for solving the problem]

[0007] The metal magnetic particles of the present invention are metal magnetic particles having an oxide layer provided on the surface of an alloy particle containing Fe and Si, wherein the oxide layer has, from the alloy particle side, a first oxide layer, a second oxide layer, and a third oxide layer, and in a line analysis of element content using a scanning transmission electron microscope-energy dispersive X-ray analysis, the first oxide layer is a layer in which the Si amount has a maximum value, the second oxide layer is a layer in which the Fe amount has a maximum value, and the third oxide layer is a layer in which the Si amount has a maximum value.

[0008] The inductor of the present invention is characterized by comprising the metal magnetic particles of the present invention.

[0009] The method for producing metal magnetic particles of the present invention includes the steps of: mixing raw material particles having a Si oxide film and an Fe oxide film on the surface of alloy particles containing Fe and Si from the alloy particle side; hydrolyzing and drying the Si alkoxide to form coated particles having a coating film containing silicon oxide formed thereon; and heat-treating the coated particles in an oxidizing atmosphere to form an oxide layer on the surface of the alloy particles, wherein the average thickness of the coating film is 10 nm or more and 30 nm or less, and the heat treatment temperature is 750°C or more and 850°C or less.

[0010] The method for manufacturing a metal magnetic core of the present invention includes the steps of: mixing raw material particles having a Si oxide film and an Fe oxide film on the surface of alloy particles containing Fe and Si from the alloy particle side; hydrolyzing and drying the Si alkoxide to form coated particles having a coating film containing silicon oxide formed thereon; molding the coated particles; and heat-treating the molded body of the coated particles in an oxidizing atmosphere to form an oxide layer on the surface of the alloy particles, wherein the average thickness of the coating film is 10 nm or more and 30 nm or less, and the heat treatment temperature is 750°C or more and 850°C or less. [Effects of the Invention]

[0011] According to the present invention, it is possible to provide metal magnetic particles and inductors with excellent insulation and DC bias characteristics, a method for manufacturing metal magnetic particles that can obtain metal magnetic particles with excellent insulation and DC bias characteristics, and a method for manufacturing metal magnetic cores that can obtain metal magnetic cores with excellent insulation and DC bias characteristics. [Brief explanation of the drawings]

[0012] [Figure 1] FIG. 1 is a cross-sectional view schematically showing an example of a metal magnetic particle of the present invention. [Figure 2] FIG. 2 is a cross-sectional view schematically showing another example of the metal magnetic particle of the present invention. [Figure 3] FIG. 3 is a STEM image of Example 1. [Figure 4] FIG. 4 is a diagram showing the results of the line analysis in Example 1. [Figure 5] FIG. 5 is a graph showing the relationship between the DC magnetic field Hsat@-20% [kA / m] (vertical axis) and the relative permeability (horizontal axis) at which the relative permeability value becomes 80% or less of the initial value in each example and comparative example. DETAILED DESCRIPTION OF THE INVENTION

[0013] The metal magnetic particles, inductors, methods for producing metal magnetic particles, and methods for producing metal magnetic cores of the present invention will be described below. However, the present invention is not limited to the following configurations, and can be appropriately modified and applied within the scope of the present invention. Note that the present invention also includes a combination of two or more of the preferred configurations of the present invention described below.

[0014] [Metal magnetic particles] The metal magnetic particles of the present invention are metal magnetic particles having an oxide layer provided on the surface of an alloy particle containing Fe and Si, wherein the oxide layer has, from the alloy particle side, a first oxide layer, a second oxide layer, and a third oxide layer, and in a line analysis of element content using a scanning transmission electron microscope-energy dispersive X-ray analysis, the first oxide layer is a layer in which the Si amount has a maximum value, the second oxide layer is a layer in which the Fe amount has a maximum value, and the third oxide layer is a layer in which the Si amount has a maximum value.

[0015] FIG. 1 is a cross-sectional view schematically showing an example of a metal magnetic particle of the present invention. As shown in FIG. 1, metal magnetic particle 1 has an oxide layer provided on the surface of alloy particle 10 containing Fe and Si. The oxide layers are, from the alloy particle 10 side, a first oxide layer 20, a second oxide layer 30 and a third oxide layer .

[0016] The alloy particles include Fe and Si. The weight ratio of Si in the alloy particles is preferably 1.5 parts by weight or more and 8.0 parts by weight or less per 100 parts by weight of the total weight of Fe and Si. If the weight ratio of Si in the alloy particles is less than 1.5 parts by weight, the loss reduction effect is poor, whereas if the weight ratio of Si in the alloy particles is more than 8.0 parts by weight, the saturation magnetization decreases significantly and the DC bias characteristics deteriorate.

[0017] The alloy particles may contain Cr in addition to Fe and Si. The alloy particles preferably contain less than 1.0 part by weight of Cr per 100 parts by weight of the total weight of Fe and Si, more preferably 0.9 part by weight or less of Cr, and even more preferably no Cr. A low Cr content improves the saturation magnetic flux density, thereby improving the DC bias characteristics.

[0018] The alloy particles may also contain, as impurity components, the same elements as the impurities contained in pure iron. Examples of impurity components include C, Mn, P, S, Cu, and Al.

[0019] The oxide layer includes, from the alloy particle side, a first oxide layer, a second oxide layer, and a third oxide layer. In this specification, the oxide layer refers to a layer in which both oxygen and metal elements (metal elements here include silicon (Si)) are counted in the line analysis of element content described below. When both oxygen and silicon are counted, it is considered that an oxide containing silicon is present, and when both oxygen and iron (Fe) are counted, it is considered that an oxide containing iron is present.

[0020] The first oxide layer is a layer in which the amount of Si is maximized in a line analysis of element content using a scanning transmission electron microscope (STEM)-energy dispersive X-ray analyzer (EDX) (hereinafter simply referred to as line analysis). The second oxide layer is a layer in which the amount of Fe is maximized in the line analysis. The third oxide layer is a layer in which the amount of Si is maximized in the line analysis.

[0021] The boundaries of the first oxide layer, the second oxide layer, and the third oxide layer are defined as follows. The first oxide layer is defined as the region from the point where the Fe content and Si content reverse (first boundary) to the point where the Si content and Fe content reverse (second boundary) in a line analysis of element content using STEM-EDX. The second oxide layer is defined as the area from the second boundary to the point (third boundary) where the Fe content and the Si content are reversed in a line analysis of the element content using STEM-EDX. The third oxide layer is defined as the area from the third boundary in the line analysis of element content using STEM-EDX to the point (fourth boundary) where the O content (oxygen content) in the line analysis is 34% of the maximum value.

[0022] Note that the "amount" of each element in line analysis of element content using STEM-EDX refers to the number of X-ray counts specific to each element (also called net counts), and does not indicate the weight ratio or atomic ratio. The magnification in STEM-EDX is set to 400,000 times.

[0023] The thickness of the first oxide layer is preferably 4 nm or more and 10 nm or less, and more preferably 5 nm or more and 8 nm or less. In a line analysis of element content using STEM-EDX, at the point where the Si content in the first oxide layer reaches a maximum, the ratio of the Fe content to the Si content (Fe content / Si content) is preferably 0.2 or more and 0.5 or less, and more preferably 0.3 or more and 0.4 or less.

[0024] The thickness of the second oxide layer is preferably 10 nm or more and 16 nm or less, and more preferably 13 nm or more and 15 nm or less. In a line analysis of element content using STEM-EDX, at the point where the Fe content in the second oxide layer reaches a maximum, the ratio of the Fe content to the Si content (Fe content / Si content) is preferably 22 or more and 27 or less, and more preferably 24 or more and 26 or less.

[0025] The thickness of the third oxide layer is preferably 9 nm or more and 15 nm or less, and more preferably 10 nm or more and 13 nm or less. In a line analysis of element content using STEM-EDX, at the point where the Si content in the third oxide layer is at its maximum, the ratio of the Fe content to the Si content (Fe content / Si content) is preferably 0.01 or more and 0.20 or less, and more preferably 0.04 or more and 0.10 or less.

[0026] The metal magnetic particles of the present invention may further have a fourth oxide layer provided on the surface of the third oxide layer. The fourth oxide layer refers to a layer in which the maximum value of the Fe content is 10% or more of the maximum value of the Fe content in the second oxide layer, as determined by line analysis, which will be described later.

[0027] FIG. 2 is a cross-sectional view schematically showing another example of the metal magnetic particle of the present invention. The metal magnetic particles 2 have an oxide layer formed on the surface of the alloy particles 10 containing Fe and Si. The oxide layers are, from the alloy particle 10 side, a first oxide layer 20, a second oxide layer 30, a third oxide layer 40 and a fourth oxide layer 50.

[0028] In the line analysis of element content using STEM-EDX, the fourth oxide layer is the layer where the Fe content is at its maximum. When the fourth oxide layer is formed, the boundary between the third oxide layer and the fourth oxide layer is defined as follows. The third oxide layer is defined as the area from the third boundary to the point (fourth boundary) where the amounts of Si and Fe are reversed in a line analysis of the element contents using STEM-EDX. The fourth oxide layer is defined as the area from the fourth boundary to the point (fifth boundary) where the O content (oxygen content) is 34% of the maximum value.

[0029] The thickness of the fourth oxide layer is preferably 4.0 nm or more and 10.0 nm or less, and more preferably 5.0 nm or more and 7.5 nm or less. In a line analysis of element contents using STEM-EDX, the ratio of the amount of Fe to the amount of Si (Fe amount / Si amount) is preferably 23 or more and 28 or less at the point where the amount of Fe in the fourth oxide layer is at its maximum.

[0030] The thicknesses of the first, second, third, and fourth oxide layers are determined by line analysis of three locations that divide the circumference of the metal magnetic particle into thirds in an enlarged image of the cross section of the metal magnetic particle observed by STEM-EDX, and the average thickness of each layer is determined. Similarly, the ratio of the Fe content to the Si content in each layer (Fe content / Si content) is determined by the average of the measured values ​​obtained by line analysis of the three locations.

[0031] In the metal magnetic particles of the present invention, adjacent oxide layers preferably have different crystallinity. For example, when the first oxide layer is amorphous, the second oxide layer is preferably crystalline, the third oxide layer is preferably amorphous, and the fourth oxide layer is preferably crystalline. Joining an amorphous oxide layer and a crystalline oxide layer increases the electrical resistance at the joint interface, so if the crystallinity of adjacent oxide layers is different, the insulation resistance can be increased.

[0032] The crystallinity of each layer can be confirmed by checking whether periodic light and dark patterns appear in the FFT image, which is a Fourier transform of the STEM image. If the material is crystalline, periodic light and dark patterns will appear in the FFT image, and if the material is amorphous, periodic light and dark patterns will not appear in the FFT image.

[0033] [Inductor] The inductor of the present invention is characterized by comprising the metal magnetic particles of the present invention.

[0034] The inductor of the present invention includes the metal magnetic particles of the present invention, and therefore has high withstand voltage and excellent DC bias characteristics.

[0035] The inductor of the present invention comprises, for example, the metal magnetic particles of the present invention and a winding disposed around the metal magnetic particles. The material, wire diameter, number of turns, etc. of the winding wire are not particularly limited and may be selected according to the desired characteristics.

[0036] The metal magnetic particles constituting the inductor of the present invention may be formed into a predetermined shape. Metal magnetic particles formed into a predetermined shape are also called metal magnetic cores. Therefore, an inductor consisting of a metal magnetic core made of the metal magnetic particles of the present invention and a winding arranged around the metal magnetic core is also an inductor of the present invention.

[0037] [Metal Magnetic Particle Manufacturing Method] The method for producing metal magnetic particles of the present invention includes the steps of: mixing raw material particles having a Si oxide film and an Fe oxide film on the surface of alloy particles containing Fe and Si from the alloy particle side; hydrolyzing and drying the Si alkoxide to form coated particles having a coating film containing silicon oxide formed thereon; and heat-treating the coated particles in an oxidizing atmosphere to form an oxide layer on the surface of the alloy particles, wherein the average thickness of the coating film is 10 nm or more and 30 nm or less, and the heat treatment temperature is 750°C or more and 850°C or less.

[0038] In the method for producing metal magnetic particles of the present invention, a coating film containing silicon oxide is formed on the surface of raw material particles having Si oxide and Fe oxide films on the surface of alloy particles, and the resulting particles are then heat-treated in an oxidizing atmosphere, whereby the Si oxide film becomes the first oxide layer, the Fe oxide film becomes the second oxide layer, and the coating film becomes the third oxide layer. For this reason, the metal magnetic particles of the present invention can be obtained by using the method for producing metal magnetic particles of the present invention.

[0039] In the method for producing metal magnetic particles of the present invention, it is possible to control whether or not a fourth oxide layer is formed by adjusting the thickness of the coating film and the conditions of the heat treatment, as will be described in detail below.

[0040] [Step of mixing raw material particles with Si alkoxide and alcohol] First, raw material particles containing Fe and Si are prepared, each having an Si oxide film and an Fe oxide film on the surface of the alloy particle from the alloy particle side. The method for forming the Si oxide film and the Fe oxide film on the surface of the alloy particles is not particularly limited, but examples thereof include a method in which fine particles of an FeSi alloy obtained by a water atomization method or the like are slowly oxidized. Gradual oxidation is a treatment in which the surface of the alloy particles is intentionally oxidized in order to prevent excessive oxidation of the alloy particles, thereby forming a surface oxide film that functions as a protective film against oxidation. For example, FeSi alloy particles are placed in a non-oxidizing atmosphere and dried, and the oxygen concentration in the atmosphere is gradually increased to gradually oxidize the surfaces of the FeSi alloy particles, forming Si oxide films and Fe oxide films on the surfaces of the alloy particles.

[0041] The alloy particles used in the method for producing metal magnetic particles of the present invention contain Si and Fe. The average particle size of the raw material particles is not particularly limited, but it is preferable that D50 is 1 μm or more and 10 μm or less. D50 is the particle size at which the cumulative volume of alloy particles is 50% as measured by laser diffraction.

[0042] Subsequently, the raw material particles are mixed with Si alkoxide and alcohol.

[0043] The Si alkoxide is preferably tetraethoxysilane. When the Si alkoxide is tetraethoxysilane, a coating film of uniform thickness is easily formed on the surface of the raw material particles. The alcohol is preferably ethanol.

[0044] When mixing the raw material particles with silicon alkoxide and alcohol, it is preferable to add polyvinylpyrrolidone as a water-soluble polymer. It is also preferable to add an aqueous ammonia solution as a basic catalyst. Silicon alkoxides are prone to hydrolysis in the presence of a basic catalyst and water.

[0045] [Step of forming coated particles] Subsequently, the Si alkoxide is hydrolyzed and dried to produce coated particles on which a coating film containing silicon oxide is formed.

[0046] At this time, the average thickness of the coating film provided on the surface of the raw material particles is set to 10 nm or more and 30 nm or less. When the average thickness of the coating film is 10 nm or more but less than 15 nm, the coating film is so thin that the Fe in the Fe oxide film is likely to diffuse to the outermost part of the coating film before densification begins.If densification begins with the Fe diffused to the outermost part of the coating film, it is thought that the Fe is pushed out to the outside of the coating film, forming a fourth oxide layer. On the other hand, if the average thickness of the coating film is 15 nm or more and 30 nm or less, the coating film is so thick that it is difficult for the Fe in the Fe oxide layer to diffuse to the outer part of the coating film before the coating film begins to densify, and it is thought that this makes it difficult for the fourth oxide layer to form. That is, if Fe diffuses to the portion close to the outside of the coating film, the Fe in the portion close to the outside of the coating film is thought to move to the outside of the coating film as the coating film densifies, forming a fourth oxide layer. On the other hand, if Fe does not diffuse to the portion close to the outside of the coating film, the Fe in the coating film is pushed back in as the coating film densifies, and the fourth oxide layer is thought not to be formed.

[0047] [Step of Heat-treating Coated Particles] The coated particles are then heat treated in an oxidizing atmosphere to form an oxide layer on the surface of the alloy particles.

[0048] The temperature of the heat treatment is 750°C or higher and 850°C or lower. It is thought that before the heat treatment temperature reaches 750°C or higher, the densification of the coating film does not progress, and Fe diffuses from the Fe oxide film into the coating film. If Fe has diffused close to the surface of the coating when the coating begins to densify, it is thought that the Fe will move to the outside of the coating and form a fourth oxide layer. On the other hand, if Fe has not diffused close to the surface of the coating when the densification of the coating progresses, the Fe that has diffused into the coating is pushed back inside as the coating densifies and is integrated with the second oxide layer.

[0049] The time for which the coated particles are heat-treated in an oxidizing atmosphere is not particularly limited, but the time for heat-treating at 750° C. or higher is preferably 10 minutes or more and 50 minutes or less. When the heat treatment time is within the above range, Fe in the Fe oxide film is likely to diffuse into the coating film and form a fourth oxide layer.

[0050] [Metal magnetic core manufacturing method] The method for manufacturing a metal magnetic core of the present invention includes the steps of: mixing raw material particles having a Si oxide film and an Fe oxide film on the surface of alloy particles containing Fe and Si from the alloy particle side; hydrolyzing and drying the Si alkoxide to form coated particles having a coating film containing silicon oxide formed thereon; molding the coated particles; and heat-treating the molded body of the coated particles in an oxidizing atmosphere to form an oxide layer on the surface of the alloy particles, wherein the average thickness of the coating film is 10 nm or more and 30 nm or less, and the heat treatment temperature is 750°C or more and 850°C or less.

[0051] In the method for producing a metal magnetic core of the present invention, a coating film containing silicon oxide is formed on the surface of raw material particles having a silicon oxide film and an iron oxide film on the alloy particle side, and the resulting coated particles are molded into a compact by heat-treating the compact in an oxidizing atmosphere. As in the method for producing a metal magnetic particle of the present invention, the iron oxide film can be diffused to the outside of the coating film to form a fourth oxide layer. Also, a metal magnetic core in which alloy particles are bonded to each other by an oxide layer can be obtained.

[0052] Of the steps constituting the method for producing a metal magnetic core of the present invention, the steps other than the molding step are common to the method for producing a metal magnetic particle of the present invention.

[0053] In the molding process, the binder resin, solvent, and coated film-forming particles may be mixed together, and then the solvent may be removed to produce a granulated powder, which may then be molded, or the mixture of the binder resin, solvent, and coated film-forming particles may be molded directly. As the binder resin, epoxy resin, silicone resin, phenol resin, polyamide resin, polyimide resin, polyphenylene sulfide resin, ethyl cellulose, etc. are preferred. Examples of the solvent include an aqueous solution of polyvinyl alcohol and terpineol.

[0054] The shape of the compact produced in the molding step is preferably a shape corresponding to the shape of the metal magnetic core to be obtained. The metal magnetic core may have, for example, a rod shape, a cylinder shape, a ring shape, a rectangular parallelepiped shape, or the like.

[0055] The molding pressure in the molding step is not particularly limited, but is preferably 100 MPa or more and 700 MPa or less.

[0056] In the method for manufacturing a metal magnetic core of the present invention, the molding step preferably includes a step of laminating and pressing green sheets containing coating film-forming particles. When the molding process includes a step of stacking and pressing green sheets containing coating film-forming particles, the distance between alloy particles in the molded body before heat treatment becomes short, making it easier to obtain a metal magnetic core in which the alloy particles are bonded to each other by an oxide layer.

[0057] A green sheet containing coated film-forming particles can be obtained, for example, by mixing a solvent containing a binder resin with the coated film-forming particles to prepare a slurry, forming the slurry into a thin film using a doctor blade method or the like, and then removing the solvent. As the binder resin and solvent, the same ones as those used when preparing the granulated powder can be suitably used.

[0058] A coil pattern or a part thereof may be formed on the green sheet containing the coating film-forming particles using a conductive paste or the like.

[0059] The molding step may also include a step of printing and drying a paste containing the coated film-forming particles. [Example]

[0060] The following examples more specifically disclose the metal magnetic particles, inductors, metal magnetic particle manufacturing methods, metal magnetic cores, and metal magnetic core manufacturing methods of the present invention, but the present invention is not limited to these examples.

[0061] Example 1 FeSi alloy particles with a weight ratio of Fe:Si=93.5:6.5 were obtained by water atomization. The surface of the obtained FeSi alloy was observed by STEM, and it was confirmed that two oxide layers with an average thickness of about 10 nm were formed on the surface of the FeSi alloy particles. Using XPS analysis, elemental analysis was performed from the surface of the FeSi alloy particles in the depth direction, and it was confirmed that there is a layer containing Fe on the surface side of the FeSi alloy particles, and a layer containing Si inside that. From the above, it was confirmed that a silicon oxide film with an average thickness of about 10 nm and an iron oxide film with an average thickness of about 10 nm were formed on the surface of the FeSi alloy particles. The obtained FeSi alloy particles were used as raw material particles.

[0062] Polyvinylpyrrolidone K30 was added to ethanol containing aqueous ammonia and FeSi alloy particles, and the mixture was stirred to obtain a mixture. Tetraethoxysilane was added dropwise to the mixture, and the mixture was stirred for 60 minutes to obtain a slurry. The slurry was filtered, washed with acetone, and then dried at 60°C to obtain coated particles. After embedding the coated particles in resin, the cross section was polished and processed using a focused ion beam (FIB) [SII SMI3050SE] to thin the sample for STEM observation. This sample for STEM observation was observed at approximately 400,000 magnification using a STEM (Hitachi High-Technologies HD-2300A), and the average thickness of the coating was confirmed to be approximately 19 nm.

[0063] 100 parts by weight of the resulting coated particles were mixed with 6 parts by weight of epoxy resin and an aqueous polyvinyl alcohol solution, dried, and sieved to obtain a granulated powder. This granulated powder was filled into a doughnut-shaped mold with an outer diameter of 20 mm and an inner diameter of 10 mm, and the mold was pressurized at 60°C under a pressure of 500 MPa for 10 seconds to form the coated particles into a ring shape with an outer diameter of approximately 20 mm, an inner diameter of approximately 10 mm, and a thickness of approximately 2 mm.

[0064] The resulting ring was degreased and sintered in a sintering furnace to obtain a sintered compact (metal magnetic core) of metal magnetic particles. Degreasing was performed in the atmosphere, and the temperature was raised to 400°C at a rate of 40°C / h, held for 30 minutes, and then naturally cooled. Firing was performed in the atmosphere, raising the temperature to a peak temperature of 800°C over 40 minutes, held for 20 minutes, and then naturally cooled. Three rings were produced: one was used for STEM-EDX measurements, one for voltage resistance measurements, and one for relative permeability and DC bias characteristics measurements.

[0065] [Line analysis by STEM-EDX] The resulting ring was embedded in resin, and the cross section was polished and processed using FIB to create a thin section to prepare a sample for STEM observation. Line analysis of the STEM measurement sample was performed using STEM and EDX (EDAX GENESIS XM4). Element analysis was performed starting from the inside of the alloy particle and proceeding toward the outside (oxide layer). The STEM magnification was 400,000 times. Figure 3 shows the STEM image, and Figure 4 shows the results of the line analysis. The vertical axis represents the count number (arbitrary unit) of the characteristic X-ray (K line) of each element, and the horizontal axis represents the distance (nm) from the starting point. Measurements were taken at intervals of 0.9 nm or less on the horizontal axis.

[0066] From FIG. 3, it was confirmed that the first oxide layer 20, the second oxide layer 30 and the third oxide layer 40 were arranged in this order on the surface of the alloy particle 10. Furthermore, it was also possible to confirm from the STEM images that the alloy particles were bonded to each other via the first oxide layer, the second oxide layer, or the third oxide layer.

[0067] From FIG. 4, the thickness of the first oxide layer is 5.5 nm, the thickness of the second oxide layer is 14.7 nm, and the thickness of the third oxide layer is 11.4 nm.

[0068] 4, it was confirmed that the oxide layer had a first oxide layer 20 in which the Si content was at a maximum, a second oxide layer 30 in which the Fe content was at a maximum, and a third oxide layer 40 in which the Si content was at a maximum. It was also confirmed that the alloy particles and the oxide layer contained almost no Cr. The ratio of the amount of Fe to the amount of Si (Fe amount / Si amount) at the point where the amount of Si in the first oxide layer reached its maximum was 0.33, the ratio of the amount of Fe to the amount of Si (Fe amount / Si amount) at the point where the amount of Fe in the second oxide layer reached its maximum was 25, and the ratio of the amount of Fe to the amount of Si (Fe amount / Si amount) at the point where the amount of Si in the third oxide layer reached its maximum was 0.070. Furthermore, it was confirmed that a fourth oxide layer was not formed, since there was no maximum Fe content exceeding 10% of the maximum Fe content of the second oxide layer 30 outside the third oxide layer 40 (at a position farther from the starting point).

[0069] In FIG. 4, the alloy particle 10 extends from the starting point to the first boundary b1 where the Fe content and the Si content are reversed. The first oxide layer 20 extends from the first boundary b1 to the second boundary b2 where the Si content and the Fe content are reversed. The second oxide layer 30 extends from the second boundary b2 to the third boundary b3 where the Fe content and the Si content are reversed. The third oxide layer 40 extends from the third boundary b3 to the fourth boundary b4, which is the point where the O content is 34% of the maximum value.

[0070] Furthermore, from the FFT image obtained by Fourier transform of the STEM image, it was confirmed that the first oxide layer was amorphous, the second oxide layer was crystalline, and the third oxide layer was amorphous.

[0071] [Measurement of voltage resistance performance] The voltage resistance performance was measured in the thickness direction of the ring. The measurement was performed using a digital ultra-high resistance / micro current meter (ADVANTEST R8340A) by clamping the ring with the attached probe and recording the resistance value [Ω] when a specified voltage was applied. The applied voltage was set at a resistance value of 10 5 The voltage was swept from 1V to 10V in 1V increments, and from 10V to 1000V in 10V increments until the resistance fell below 10 [Ω]. 5 The applied voltage [V] just before it fell below [Ω] was recorded, and the electric field strength [V / mm] was calculated by dividing the ring thickness by this voltage. The results are shown in Table 1. In addition, even at the maximum applied voltage of 1000V of the measuring device, the resistance value was 10 5 If the resistance value is not below [Ω], it is recorded in Table 1 as being equal to or greater than the value obtained by dividing the resistance value [Ω] at 1000V by the ring thickness.

[0072] [Measurement of relative permeability] After the ring was impregnated with epoxy resin to improve its mechanical strength, the relative permeability was measured using an impedance analyzer (Keysight E4991A). The relative permeability was measured at 1 MHz. The results are shown in Table 1.

[0073] [Measurement of DC superposition characteristics] Furthermore, a 0.35 mm diameter copper wire was wound 24 times around the ring, and the DC bias characteristics were measured using an LCR meter (Keysight 4284A). A DC current of 0 to 30 A was applied to the copper wire, and the relative permeability (μ value) was calculated from the obtained L value. The current value at which the μ value fell to 80% of its initial value (Isat@-20%) was obtained. From Isat@-20%, the ring size, and the number of turns of the copper wire, Hsat@-20% [kA / m], the magnetic field at which the μ value fell to 80% of its initial value, was calculated. The results are shown in Table 1. The inductor of the present invention is formed by winding a copper wire around a ring.

[0074] (Examples 2 and 3) Except for changing the pressures used to form the coated particles to 300 MPa and 100 MPa, rings were produced in the same manner as in Example 1, and the electric field strength, resistivity, relative permeability, and Hsat@-20% were determined. The results are shown in Table 1.

[0075] Example 4 The rings were produced in the same manner as in Example 1, except that the peak temperature of the heat treatment was changed from 800° C. to 780° C., and the electric field strength, resistance value, relative permeability, and Hsat@-20% were determined. The results are shown in Table 1.

[0076] (Comparative Examples 1 to 3) Rings were produced in the same manner as in Examples 1 to 3, except that raw material particles were used instead of the coated film-forming particles and the heat treatment temperature was changed to 690° C., and the electric field strength, resistivity, relative permeability, and Hsat@-20% were measured. The results are shown in Table 1.

[0077] (Comparative Examples 4 to 6) Except for using raw material particles instead of the coated film-forming particles, rings were produced in the same manner as in Examples 1 to 3, and the electric field strength, resistance value, relative permeability, and Hsat@-20% were measured. The results are shown in Table 1.

[0078] [Table 1]

[0079] The results in Table 1 show that the metal magnetic particles of the present invention have higher electric field strength and superior voltage resistance compared to Comparative Examples 1 to 6, which do not have coated film-formed particles. Furthermore, comparing Comparative Examples 1 to 3 with Comparative Examples 4 to 6, it is believed that when raw material particles without a coating film were heat-treated at 800°C, the oxidation of the alloy particles progressed, resulting in a decrease in relative permeability.

[0080] The relationship between Hsat@-20% [kA / m] (vertical axis) and relative magnetic permeability (horizontal axis) for each example and comparative example is shown in Figure 5. From Figure 5, it was confirmed that the plot position for the metal magnetic particles of Examples 1 to 3 is shifted to the upper right compared to the metal magnetic particles of Comparative Examples 1 to 3 and 4 to 6. This confirms a tendency for the Hsat@-20% value to improve when the relative magnetic permeability is approximately the same, demonstrating that the metal magnetic particles of the present invention have excellent DC bias characteristics.

[0081] [Relationship between heat treatment temperature and inductor Rdc] (Comparative Example 7) The laminated inductor according to Comparative Example 7 was fabricated by the following steps.

[0082] First, 100 parts of the coated particles prepared in Example 1 were mixed with 2.5 parts of polyvinyl acetate as a binder resin and terpineol as a solvent to form a slurry. Then, a magnetic sheet having a thickness of approximately 12 μm was obtained by a doctor blade method.

[0083] A magnetic sheet was subjected to a specified laser processing to form via holes with a diameter of 20 μm or more and 30 μm or less. The via holes were filled with Ag paste on the specific sheet with the via holes, and a specified conductor pattern (coil conductor) with a thickness of about 11 μm for surrounding the coil was screen-printed and dried to obtain a coil sheet.

[0084] The coil sheets were laminated in a predetermined order so that after singulation, a coil having a winding axis parallel to the mounting surface would be formed inside the laminate.

[0085] The laminate was molded under a pressure of 690 MPa, then heat-treated at 690°C, and cut to a predetermined chip size to obtain individual chips.

[0086] The chip was immersed at an angle into a layer of Ag paste stretched to a specified thickness and baked to form base electrodes for the external electrodes on the four surfaces (main surface, end surfaces, and both side surfaces) of the laminate.

[0087] An Ni film and an Sn film having a predetermined thickness were successively formed on the base electrode by plating to form an external electrode. The laminated inductor according to Comparative Example 7 was fabricated by the above procedure.

[0088] Example 5 The laminated inductor according to Example 5 was fabricated in the same manner as in Comparative Example 7, except that the temperature of the heat treatment was changed to 800°C.

[0089] Using an LCR meter, the DC resistance (Rdc) of the multilayer inductors according to Comparative Example 7 and Example 5 was measured. Measurements were carried out using 20 samples for each and the average value was calculated. The results are shown in Table 2.

[0090] [Table 2]

[0091] The results in Table 2 confirm that the DC resistance (Rdc) decreases when the heat treatment temperature is changed from 690°C to 800°C. This is thought to be because changing the heat treatment temperature from 690°C to 800°C causes the Ag paste used in the internal electrodes to sinter more, reducing the resistivity and decreasing the DC resistance (Rdc). Therefore, in inductors in which the internal electrodes are formed by sintering, it is thought that the DC resistance (Rdc) is low and power loss due to heat generation is small. [Explanation of symbols]

[0092] 1, 2 Metal magnetic particles 10 Alloy particles 20 First oxide layer 30 Second oxide layer 40 Third oxide layer 50 Fourth oxide layer b1 first boundary b2 second boundary b3 third boundary b4 4th boundary

Claims

1. A metal magnetic core is formed by bonding metal magnetic particles, each of which has an oxide layer provided on the surface of an alloy particle containing Fe and Si, to each other through the oxide layer, the oxide layer has, from the alloy particle side, a first oxide layer, a second oxide layer, and a third oxide layer, In a line analysis of elemental content using scanning transmission electron microscopy-energy dispersive X-ray analysis, the first oxide layer is a layer in which the amount of Si has a maximum value, the second oxide layer is a layer in which the Fe amount has a maximum value, 2. A metal magnetic core comprising: a first oxide layer and a second oxide layer, the second oxide layer being a layer in which the amount of Si is maximized;

2. 2. The metal magnetic core according to claim 1, wherein a weight ratio of Si in the alloy particles is 1.5 parts by weight or more and 8.0 parts by weight or less per 100 parts by weight of the total weight of the Fe and the Si.

3. 3. The metal magnetic core according to claim 1, wherein the alloy particles contain less than 1.0 part by weight of Cr per 100 parts by weight of the total weight of the Fe and the Si.

4. the oxide layer further comprises a fourth oxide layer provided on a surface of the third oxide layer, In a line analysis of elemental content using scanning transmission electron microscopy-energy dispersive X-ray analysis, 4. The metal magnetic core according to claim 1, wherein the fourth oxide layer is a layer in which the Fe content takes a maximum value.

5. In a line analysis of elemental content using scanning transmission electron microscopy-energy dispersive X-ray analysis, 5. The metal magnetic core according to claim 1, wherein the maximum value of the Fe content in the first oxide layer is greater than the maximum value of the Fe content in the third oxide layer.

6. In a line analysis of elemental content using scanning transmission electron microscopy-energy dispersive X-ray analysis, 6. The metal magnetic core according to claim 1, wherein the minimum value of the Fe content of the first oxide layer is greater than the minimum value of the Fe content of the third oxide layer.

7. In a line analysis of elemental content using scanning transmission electron microscopy-energy dispersive X-ray analysis, The metal magnetic core according to any one of claims 1 to 6, wherein the ratio of the Fe content to the Si content (Fe content / Si content) at the point where the Fe content of the second oxide layer is at its maximum value is 22 or more and 27 or less.

8. In a line analysis of elemental content using scanning transmission electron microscopy-energy dispersive X-ray analysis, The metal magnetic core according to any one of claims 1 to 7, wherein at the point where the Si content of the third oxide layer is at its maximum value, the ratio of the Fe content to the Si content (Fe content / Si content) is 0.01 or more and 0.20 or less.

9. An inductor comprising the metal magnetic core according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • JP1973066971A

  • JP1975082002A

  • Magnetic material, electronic component, and manufacturing method of magnetic material

    JP2019009307A

  • Soft magnetic metal powder, powder magnetic core and magnetic component

    JP2019160943A